PsycEXTRA Dataset 2010
DOI: 10.1037/e602332012-001
|View full text |Cite
|
Sign up to set email alerts
|

How Do Women Weather Economic Shocks? A Review of the Evidence

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
(23 reference statements)
0
15
0
1
Order By: Relevance
“…Our effort to examine economic coping behavior builds on a long-standing literature that has looked at how American households react to economic shocks. For example, research has found that women and mothers may modify their behavior differently than men during economic downturns, but that gender differences are influenced by the economic standing of families (Sabarwal et al 2011 ). Research has also documented the struggles of racial and ethnic minorities and the disparities in savings and intergenerational wealth that help buffer emergency situations or unanticipated job loss (Darity and Mullen 2020 ; Pfeffer and Killewald 2017 ).…”
Section: Evidence Of Covid-19’s Impact On Latino Americans’ Financialmentioning
confidence: 99%
“…Our effort to examine economic coping behavior builds on a long-standing literature that has looked at how American households react to economic shocks. For example, research has found that women and mothers may modify their behavior differently than men during economic downturns, but that gender differences are influenced by the economic standing of families (Sabarwal et al 2011 ). Research has also documented the struggles of racial and ethnic minorities and the disparities in savings and intergenerational wealth that help buffer emergency situations or unanticipated job loss (Darity and Mullen 2020 ; Pfeffer and Killewald 2017 ).…”
Section: Evidence Of Covid-19’s Impact On Latino Americans’ Financialmentioning
confidence: 99%
“…However, it is likely because they are uneducated that they cannot gain the skills necessary to access many jobs. This results in a self-fulfilling prophesy and the vicious cycle continues (Sabarwal, Sinha, and Buvinic 2010; Summers 1994). Public funding for education takes some of the burden off of families in paying for the education of both sons and daughters.…”
Section: Social Welfare Policies and Women‘s Economic And Political Smentioning
confidence: 99%
“…As discussed above, social spending aids women by removing barriers to their participation in public life. For instance, education spending enables women to gain skills and have expanded opportunities (Edin and Lein 1997; Sabarwal, Sinha, and Buvinic 2010; Summers 1994). A basic example of this is the role of education in providing simple literacy skills necessary to stand for public office (Shvedova 2005).…”
Section: Social Welfare Policies and Women‘s Economic And Political Smentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon that women's employment increases during economic crisis while men's decreases is found during several crisis episodes in Latin America and Asia. For a survey of these studies, refer to Sabarwal et al (2011).…”
Section: Acknowledgmentmentioning
confidence: 99%